2022
DOI: 10.1515/zfs-2022-2008
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting gender-fair language and stereotypes – A comparison of word pairs, capital I forms and the asterisk

Abstract: In this paper we replicated two influential studies on gender-fair language that investigated how gender-fair language influences stereotype perception and recall of exemplars. We also updated the original studies to assess new forms of gender-fair language. A first set of studies replicated Gabriel et al. (2008) by eliciting gender proportion ratings for occupational nouns from adult German native speakers for word pairs, capital I forms and the asterisk. Results were mixed with effects mainly for female-bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…This finding is in line with previous findings in that it supports the idea that generic masculines are not gender-neutral but biased towards the masculine (e.g. Braun et al, 1998;Rothermund, 1998;Heise, 2000;Rothmund & Scheele, 2004;Gygax et al, 2008;Irmen & Kurovskaja, 2010;Sato et al, 2016;Misersky et al, 2019;Keith et al, 2022;Schunack & Binanzer, 2022).…”
Section: R a F Tsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in line with previous findings in that it supports the idea that generic masculines are not gender-neutral but biased towards the masculine (e.g. Braun et al, 1998;Rothermund, 1998;Heise, 2000;Rothmund & Scheele, 2004;Gygax et al, 2008;Irmen & Kurovskaja, 2010;Sato et al, 2016;Misersky et al, 2019;Keith et al, 2022;Schunack & Binanzer, 2022).…”
Section: R a F Tsupporting
confidence: 92%
“…Such investigations make use of a diverse range of behavioural methods (e.g. Braun, Gottburgsen, Sczesny & Stahlberg, 1998;Rothermund, 1998;Heise, 2000;Stahlberg, Sczesny & Braun, 2001;Rothmund & Scheele, 2004;Irmen & Kurovskaja, 2010;Sato, Öttl, Gabriel & Gygax, 2016;Misersky, Majid & Snijders, 2019;Keith, Hartwig & Richter, 2022;Schunack & Binanzer, 2022). The main finding this body of research boils down to is that generically used masculine role nouns in German are indeed not comprehended as gender-neutral, even though the intention of their use may be a gender-neutral one.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, similar to the present studies, results on the question whether person-specific factors moderate the influence of linguistic gender form on cognitive gender representations are not very consistent. Sometimes no moderation was found (e.g., Körner et al, 2022;Schunack & Binanzer, 2022) while at other times, person-specific factors did moderate gender biases or spontaneous use of socalled gender-fair forms (e.g., Gabriel & Mellenberg, 2004;Gustafsson Sendén et al, 2015;Koeser & Sczesny, 2014;Lindqvist et al, 2019;Sczesny et al, 2015). The nature of the experimental paradigm might have contributed to these differences.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in the German gender star form, an asterisk meant to symbolize all-that is, also nonbinary-gender identities is inserted after the word stem and before the (typically feminine) suffix (e.g., Musiker*innen; "musicians"). Empirically, these three forms have been found to lead to stronger representations of women compared to the generic masculine (Keith et al, 2022;Schunack & Binanzer, 2022;Tibblin et al, 2022;Xiao et al, 2023;Zacharski & Ferstl, 2023), frequently even to a female bias, that is stronger representations of women than men (e.g., Heise, 2000;Körner et al, 2022;Rothmund & Scheele, 2004;Tibblin et al, 2023).…”
Section: Processing Gender Forms In Written Languagementioning
confidence: 99%
“…3 Both strategies have been studied empirically using different experimental methods with the aim of investigating their effects on speakers' mental representations of gender. As for the re-feminisation strategy, studies have repeatedly found that complete and contracted double forms increase representation of women in German (e.g., Braun et al, 2005;Hansen et al, 2016;Irmen & Roßberg, 2004;Körner et al, 2022;Schunack & Binanzer, 2022) and in French (e.g., Brauer & Landry, 2008;Tibblin et al, 2023;Xiao et al, 2022). The few existing studies on French gender-neutral forms indicate that these forms are successful in attenuating the male bias induced by the masculine form, at least as long as there is no interference with stereotype information (e.g., Kim et al, 2022;Richy & Burnett, 2021;Tibblin et al, 2023).…”
Section: French Gffs and Their Effects On Mental Representations Of G...mentioning
confidence: 99%